Waste less time on Facebook — follow Brilliant.
×

trigonometry ratio and their relation

PROVE THAT SIN^4THETA- COS^4THETA=2SIN(SQ)THETA-1

Note by Rishit Joshi
4 years ago

No vote yet
2 votes

Comments

Sort by:

Top Newest

We have-

\(LHS = Sin^4\theta - Cos^4\theta\)

\(= (Sin^2\theta + Cos^2\theta)(Sin^2\theta - Cos^2\theta)\)

\(= Sin^2\theta - Cos^2\theta\)

\(= Sin^2\theta - (1 - Sin^2\theta)\)

\(= 2Sin^2\theta - 1 = RHS.\)

Hence Proved. Akshat Jain · 4 years ago

Log in to reply

@Akshat Jain Yeah @Akshat ! Correct ! Priyansh Sangule · 4 years ago

Log in to reply

@Akshat Jain thanx bro Rishit Joshi · 4 years ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...